Comparative Analysis Of Workload On Employee Performance At Pt Dinamik Putra Perkasa Palembang And CV Honda Lestari - Basri, Anisa; Harahap, Lily Rahmawati; Effendi, RY. (Jurnal Fokus Manajemen, 2025)
This study aims to examine differences in workload levels on employee performance at PT Dinamik Putra Perkasa Palembang and CV Honda Lestari Motorindo. The approach used is the independent Sample t-test method with saturated sampling technique, involving 35 respondents each from both companies. The results of validity, reliability, and normality testing show that the data collectedare eligible for further analysis. Based on the t-test results, a significance value of 0,000 was obtained which is smaller than 0.05, indicating a significant difference between the two companies. The average workload and employee performance were recorded higher at PT Dinamik Putra Perkasa . The findings of this study indicate that differences in the work system applied affect employee performance.